Physical, affective and psychological determinants of athlete burnout - Moen, F.; Myhre, K.; Klöckner, C. A.; Gausen, C.; Sandbakk, O. (The Sport Journal, 2017)
This article examined how training load, illness and injuries, perceived performance, affect and worry predict athlete burnout in sport. A sample of 358 Norwegian junior elite athletes from a variety of sports with cross country skiing (28 %), soccer (22 %) and biathlon (13 %) being those most frequently reported participated in the investigation. The results show that the theoretical model in this study explains 57% of the variance in athlete burnout, and the direct effects on athlete burnout are mainly derived from the variables positive affect, worry and negative affect. In addition, our model also shows that performance, illness/injuries and worry indirectly affect athlete burnout through the mediating variables in the model. The results are discussed in regard of applied implications and possible future research.